Synthesis of zero-valent iron supported with graphite and plastic based carbon from recycling spent lithium ion batteries and its reaction mechanism with 4-chlorophenol in water. (1st January 2023) - Gao, Guilan; Li, Zhuoxiang; Chen, Shuai; Belver, Carolina; Lin, Donghai; Li, Zixiang; Guan, Jie; Guo, Yaoguang; Bedia, Jorge
Abstract: Graphite and plastic recycled from spent lithium ion batteries were used to synthesize zero-valent iron/graphite (ZVI/G), zero-valent iron/plastic-based carbon (ZVI/P), and zero-valent iron/graphite and plastic-based carbon (ZVI/GP) with iron oxide through carbothermic reduction. The aim of preparing these catalysts is to improve the performance of ZVI in the removal of 4-chlorophenol (4-CP) in water through heterogeneous Fenton reactions. The structural and textural properties of materials were characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, N2 adsorption/desorption, Fourier transform infrared spectroscopy, and X-ray photoelectron spectroscopy. The synthesis procedure successfully disperses ZVI particles on the synthesized materials. The combination of graphite and plastic-based carbon in ZVI/GP resulted in the best 4-CP removal performance. The degradation data fitted pseudo-first-order kinetic well. The Increase in the ZVI/GP dosage and the hydrogen peroxide concentration enhanced the 4-CP removal due to the increase in the amount of Fe 2+ ions and reactive sites. Acidic pH increased the 4-CP removal percentage due to the high H + concentration. The increase in the temperature favored the OH formation and facilitated the 4-CP removal. The reaction energy of ZVI/GP reaches 53.54 kJ mol −1, which is competitive among the iron catalysts reported in literatures, and showing the 4-CP removal is reaction-controlled process. This study shows a promising way of recycling graphite and plastic in spent LIBs to prepare ZVI materials for wastewater treatment with the advantages of improved conductivity by graphite and added functional groups by plastic based carbon. Graphical abstract: Image 1 Highlights: ZVI/GP was prepared with graphite and plastic from spent LIB and iron oxide. Dispersed ZVI particles on graphite and plastic based carbon were obtained. Removal of 4-CP by heterogeneous Fenton reactions. Graphite offers conductivity and plastic based carbon serve surface functional bonds. The reaction energy of ZVI/GP reaches 53.54 kJ mol −1 .